Re-interpreting the case study approach in architectural research - Salura, Purnama; Clarissa, Stephanie (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The case study is a research approach carried out in a natural, holistic, and in-depth setting about a unique, best practice, and bounded phenomenon. Even though it was rooted in social sciences, the case study has characteristics that are almost the same as a process of studying past architectural works (precedent studies) that have long been carried out in architecture. Unfortunately, precedent studies are sometimes only limited to documentation and descriptions of architectural works as physical objects, without critical, in-depth and holistic analysis of the decisions behind the design decisions of a precedent. On the other hand, previous research that discussed the case study approach in architecture tended to understand this approach as just a social research method that was simply applied in architectural research. Therefore, it is crucial to understand the terms of the 'case' itself. This research aims to provide a complete and in-depth understanding of the case study approach, to filter and elaborate this approach for architectural research. This research examines and elaborates on credible and recent literature on case study, both in social and architectural research. Elaboration from the literature review is used to formulate an operational framework based on architectural function-form-meaning. It is hoped that the results of this research will enrich architectural knowledge. The in-depth understanding is ultimately beneficial for improving existing architectural practices and becoming a source of knowledge for the general public.